The influence of chronic stress on periodontal tissues in orthodontic patients in conditions of martial law - Ye.Ye. Vyzhenko; V.D. Kuroiedova; P.S. Korobov; L.B. Halych (Medičnì Perspektivi, 2024)
There is a close relationship between the condition of periodontal tissues and maloccluson. Timely functional diagnosis of changes that occur in periodontal tissues during orthodontic tooth movement is an important link in the prevention of periodontal diseases during orthodontic treatment. At the present time, special attention is paid to the problem of the influence of "war stress" on the maxillo-facial system of a human. Aim of the was work to study the changes in the state of periodontal supporting tissues in orthodontic patients according to periotestometry data during the last 15 years and in the conditions of martial law. Periotestometry of teeth in orthodontic patients was performed before the start of treatment with the Periotest device. All patients were divided into 4 groups according to the results in different years of the study. A total of 136 patients participated in the study. The biggest discrepancies when comparing periotestometry indicators were found between the data of the control and fourth group (in conditions of martial law) and an increase in the indicators of tooth mobility with a statistically significant difference of p<0.001 was proven. When comparing the indicators of groups 2 and 4 for most teeth, the statistically significant difference was from p<0.05 to p<0.001. When comparing the data of the tooth periotest in patients of groups 3 and 4, the indicators of tooth mobility also increased, although within the limits of statistical error (p>0.05). Over the past 15 years, a steady trend to increase in the mobility of all teeth on both jaws has been established. The largest changes in indicators were found in the dynamics of the fifteen-year follow-up (2008 to 2023) between people with an orthognathic bite of the control group and patients of the 4th group with malocclusion. Such changes may be related to the social and psycho-emotional stress that a person constantly experiences in conditions of martial law.